Esprit de corps - Singh, Ranjit; VStudios ([S.l.] : VStudios, 2008)
Ranjit Singh delivers an impassioned, insightful and immensely informative motivational training as he talks about the care values that will change the way you look at your team. Drawing from his personal tales of triumph and challenges, Ranjit Singh believes that in business that transforms, it is crucial to develop Espirit-de-corpd (spirit of the team) to withstand whatever roadblocks you find along the way
Title from title screen
DVD format
Keywords: Teams in the workplace; Strategic planning; Multilevel marketing; Direct marketing